Revision of the family Carabodidae (Acari: Oribatida) III. Redefinition of Meriocepheus peregrinus Aoki, 1973; Bathocepheus concavus Aoki, 1978; and Opisthocepheus kirai Aoki, 1976 - Fernández, Néstor Alfredo (2013)
Meriocepheus peregrinus Aoki, 1973; Bathocepheus concavus Aoki, 1978; and Opisthocepheus kirai Aoki, 1976 are redescribed and illustrated based on adult specimens studied by means of optical microscopy. The three genera are redefined.